OPTIMALISASI PERLINDUNGAN KONSUMEN PANGAN INDUSTRI RUMAH TANGGA MELALUI PENGUATAN SISTEM KEAMANAN PANGAN TERPADU (Bagian kedua) - Bambang Hermanu (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
This study examines further from previous studies that have discussed the regulation and form of food consumer protection through the realization of an optimal integrated food safety system. With the sociological juridical approach method, it not only examines normative matters, but empirical data collection is also carried out in the field through observation and comprehensive interviews with related parties as well as qualitatively analysed. The thing that is more emphasized from the results of this research is focused on the aspects of the realization of the protection of home industry food consumers through strengthening the food safety system more broadly and reaching all levels of society. The results of this study in principle put more emphasis on efforts to increase the strengthening of working relationships balanced with proportional clarity of the main tasks and functions of the stakeholder agencies, so that the final target leads to a more effective, strong and reliable consumer protection.